The Lithuanian version of the Burnout Assessment Tool (BAT-LT): psychometric characteristics of the primary and secondary symptoms scales - Lazauskaitė-Zabielskė, Jurgita; Žiedelis, Arūnas; Jakštienė, Rita; Urbanavičiūtė, Ieva; De Witte, Hans (Frontiers in Psychology, 2023)
The Burnout Assessment Tool (BAT) is a new measure of burnout that was developed to address the shortcomings of existing burnout instruments. This study investigates the psychometric properties of the Lithuanian version of the Burnout Assessment Tool (BAT-LT). In total, 408 adult workers were surveyed (the mean age was 35.94 years; 68.6 per cent were female; 43.9 per cent held managerial positions). Participants came from different sectors of economic activity. The results showed that BAT-LT had good factorial validity, indicating that BAT-LT’s four subscales (exhaustion, cognitive impairment, emotional impairment, and mental distance) can be combined into a single burnout score. Moreover, Cronbach’s alpha values indicate good reliability for all six core and secondary burnout symptoms scales. Furthermore, the results confirmed that BAT-LT could be differentiated from job boredom, workaholism, work engagement and depression. Finally, measurement invariance across managerial status and the sector was observed. The results of this study provide solid evidence for BAT-LT’s reliability and factorial and construct validity.